Practice of digitizing the observation logs of earthquake monitoring stations in Jiaxing City - Wei Zhong (地震科学进展, 2023)
In order to improve the modern management level of unattended seismic monitoring stations in cities and counties, standardize the management of observation logs in stations, and improve the display of seismic monitoring work in cities and counties, Jiaxing Seismic Survey and Prevention Center actively explored the implementation of digital management of seismic monitoring stations through the development of the “Digital Observation Log Project of Seismic Monitoring Stations”. This paper mainly introduces the basic ideas and technical approaches of the research and development of the project, and briefly describes the main functions of the system. The implementation of the project can effectively solve the drawbacks of the traditional paper-based observation logs of seismic monitoring stations, and realize the digital management of the basic information of seismic monitoring stations and daily operation and maintenance. The project also builds the QR code for station information, effectively giving full play to the role of city and county monitoring stations in science popularization and publicity in earthquake prevention and disaster reduction, emergency response, disaster prevention culture and other aspects, and expanding the social service function of stations.